Effectiveness of Dental Joyful Learning Videos on Oral Health Knowledge in Children with Intellectual Disabilities in Paedagogia Special School in Surabaya - Syaima Istikhamah; Ratih Larasati; Imam Sarwo Edi; Ida Chairanna Mahirawatie (International Journal of Advanced Health Science and Technology, 2025)
Children with intellectual disabilities often experience substantial challenges in understanding and performing effective oral hygiene practices, which contributes to a disproportionately high prevalence of dental caries and unmet dental treatment needs. Limited cognitive abilities, reduced motor skills, and low health literacy further hinder their ability to maintain proper oral hygiene. Addressing these gaps requires educational approaches that are accessible, engaging, and tailored to their learning characteristics. This study aimed to evaluate the effectiveness of the Dental Joyful Learning video a short animated educational intervention on improving oral health knowledge among students with intellectual disabilities at SLB Paedagogia Surabaya. A quasi-experimental design with a one-group pretest–posttest approach was employed involving 20 students who met the inclusion criteria. Participants completed a structured Guttman-scale questionnaire before and after a single 3-minute video intervention. Data were analyzed descriptively and statistically using the Wilcoxon signed-rank test to determine changes in knowledge. The findings demonstrated a marked improvement in oral health knowledge following the intervention. Prior to the video exposure, 75% of participants fell within the poor knowledge category, with an average score of 34%. After the intervention, 80% of participants reached the good category, with the mean score rising significantly to 83%. The Wilcoxon test yielded a p-value of 0.000 (<0.05), confirming a statistically significant increase in knowledge. In conclusion, the Dental Joyful Learning video proved effective in enhancing oral health knowledge among children with intellectual disabilities. The use of concise, visually engaging, and cognitively appropriate audiovisual media can serve as a practical and impactful educational strategy in special-needs settings. This study highlights the value of tailored digital health education tools in promoting better understanding and supporting preventive oral health behaviors in this vulnerable population.